CITRA TUBUH DAN FAKTOR PEMBENTUK CITRA TUBUH PEREMPUAN EMERGING ADULT YANG MENGALAMI KENAIKAN BERAT BADAN SIGNIFIKAN KETIKA REMAJA - Isabella Pramono; Nanda Rossalia (MANASA, 2023)
Â Women often receive comments about their bodies as they gain weight, which increases the risk of developing a negative body image and damage the identity formation process during adolescence. These obstacles will impact the emerging adulthood developmental stages. This study aims to describe body image and body image formation factors in emerging adult women who experienced significant weight gain from being underweight during adolescence. Qualitative research was conducted, involving three adult female participants aged 18-25 years, who were classified as underweight during adolescence, experienced significant weight gain, had either underweight or normal Body Mass Index (BMI), and had a negative body image based on the Multidimensional Body-Self Relational Questionnaire-Appearance Scales (MBSRQ-AS). The three participants were selected through purposive criterion sampling. Data was collected through semi structured interviews, which were then analyzed using thematic analysis. The results showed that all three participants were dissatisfied with specific body parts due to the desire to achieve their ideal body weight. This dissatisfaction affected theparticipantsâ€™ efforts to present themselves and control their weight. These views were formed from individual experiences during adolescence, which persisted into emerging adulthood and were greatly influenced by interpersonal factors and cultural socialization factors.